Pengaruh Waktu Fermentasi terhadap Produksi Biogas Menggunakan Digester Dua Tahap pada Berbagai Konsentrasi Palm Oil-Mill Effluent dan Lumpur Aktif - Siti Mujdalipah; Salundik Dohong; Ani Suryani; Amalia Fitria (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
The production of biogas from palm oil-mill effluent (POME) and activated sludge derived from fresh cow feces through a few stages of the reaction at a single digester inhibited the reaction of anaerobic fermentation. The development of the biogas production process using two stages digester can optimize the anaerobic fermentation reactions. The aims of this research was to know the fermentation time effect toward biogas production in two stage digester. The study was done in three stages, that are subtrate analysis, biogas production by using two stages digester, and data analysis. The study was done in three combinations of feedstock which were POME concentrations of 90, 80, and 70% and activated sludge concentrations of 10, 20, and 30%. A mixture of POME and activated sludge at 0.35 L/day for 40 days were fed into two stages digester. Combination POME of 90% and activated sludge of 10% was denoted 90LC:10LA, combination POME of 80% and activated sludge of 20% was denoted 80LC:20LA, and combination POME of 70% and activated sludge of 30% was denoted 70LC:30LA. The result showed the fermentation time gave significant effect toward biogás production in the second stage digester. All combinations showed the upward trend in the volume of biogás during fermentation. Combination 80LC:20LA showed the highest volume increases from 1st digester to 2nd digester, that was 121,29%. Fermentation time in 2nd digester for all combinations (90LC:10LA, 80LC:20LA, and 70LC:30LA) gave significant effects toward pH where pH increased for 40 days the fermentation time. The highest volume of biogas was reached when POME and activated sludge in combination 90LC:10LA. It was 11.35 L.ABSTRAKProduksi biogas dari limbah cair pabrik minyak kelapa sawit dan lumpur aktif yang berasal dari feses sapi segar melalui beberapa tahap reaksi pada satu digester menyebabkan terhambatnya reaksi fermentasi anaerobik. Pengembangan proses produksi biogas menggunakan digester dua tahap dapat mengoptimalkan reaksi fermentasi anaerobik. Tujuan penelitian ini yaitu untuk mengetahui pengaruh waktu fermentasi terhadap produksi gas dari perlakuan kombinasi substrat (limbah cair dan lumpur aktif) pada digester 2 tahap. Penelitian terdiri dari tiga tahap, yaitu 1) analisis subtrat, 2) proses produksi biogás menggunakan digester 2 tahap, dan 3) analisis data. Penelitian ini menggunakan tiga kombinasi bahan baku, yaitu POME sebesar 90, 80, dan 70 % dan lumpur aktif sebesar 10, 20, dan 30%. Kombinasi POME 90% dan lumpur aktif 10% dilambangkan 90LC:10LA, kombinasi POME 80% dan 20% lumpur aktif dilambangkan 80LC:20LA, dan kombinasi POME 70% dan 30% lumpur aktif dilambangkan 70LC:30LA. Bahan baku diumpankan ke dalam digester dua tahap dengan laju alir 0,35 L/hari selama 40 hari. Hasil menunjukkan bahwa waktu fermentasi memberikan pengaruh yang nyata terhadap produksi biogas pada digester tahap II. Seluruh kombinasi memperlihatkan tren peningkatan volume biogás selama waktu fermentasi. Prosentase peningkatan volume biogas tertinggi antara digester I dan digester II sebesar 121,29 % terjadi pada kombinasi 80LC:20LA. Waktu fermentasi pada digester tahap II untuk kombinasi 90LC:10LA, 80LC:20LA, dan 70LC:30LA juga memberikan pengaruh yang nyata terhadap nilai pH. Volume biogas tertinggi selama 40 hari waktu fermentasi didapatkan pada kombinasi 90LC:10LA, yaitu sebesar 11,35 liter.